Flexibilisation without hesitation? Temporary contracts and Workers' satisfaction - Adrian Chadi; Clemens Hetschko (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
Fixed-term contracts are often considered a key policy tool for increasing employment. As we show that contract limitation lowers job satisfaction using data from the German Socio-Economic Panel study, we detect a drawback of promoting temporary employment that has not been identified so far. We find that the honeymoon-hangover effect of a new job must be taken into account to reveal this result. We examine reasons why employees suffer from temporary contracts and analyse the Flexicurity idea of compensating workers with security. Our findings contribute to research on workers' well-being as well as to the debate on labour market flexibilisation.
Keywords: J28; J41; 330; labour market flexibilisation; job satisfaction; temporary contracts